Posisi Media Cetak di Tengah Perkembangan Media Online di Indonesia - Satria Kusuma (Jurnal InterAct, 2016)
Currently, there are dozens and even hundreds of print media in the United States which are waiting for their turn to be closed. Popular newspapers such as The Washington Post and the Wall Street Journal printed edition are now distributed for free in most of the town centers in the United States. In Indonesia, Sinar Harapan newspaper closed its doors on January 1, 2016, following the dailies, Soccer, National Journal, and editorial magazines such as Prospects, and Fortune. Even though newspaper readership continues to decline in Indonesia, it does not necessarily make the printed media entirely switch to online media. In order to survive, the conventional media should be able to maintain credibility and trust in presenting the information. Credibility and public trust can only be built by the spirit of professionalism of journalists who adhere to the ethics of journalism which presents the factual and properly verified information. This is a strong bid for the print media to survive. The media industry especially newspapers need to make changes to survive. Strategic change is important to be done to make the newspaper remain in existence. Newspapers should be able to define its base on its medium. The newspapers should not just be a paper. The strength and value do not only come at the control of content and distribution.